Fulminant Type 1 Diabetes Mellitus Caused by Drug Reaction With Eosinophilia and Systemic Symptoms (DRESS): A Case Report and Review of the Literature - Zhu, Bizhen; Wu, Jinzhun; Chen, Guobing; Yang, Yungang; Yi, Cuili (Frontiers in Endocrinology, 2019)
Drug reaction with eosinophilia and systemic symptoms (DRESS), also known as drug-induced hypersensitivity syndrome (DIHS) is a rare, severe cutaneous adverse drug reaction characterized by fever, skin rashes, lymphadenopathy, leukocytosis with eosinophilia, and/or atypical lymphocytosis, and multiple visceral organ involvement. Moreover, patients with DRESS are at risk of developing autoimmune diseases including thyroiditis, diabetes mellitus (DM), and systemic lupus erythematosus (SLE), etc. several weeks or months after the initial resolution. We described a 9-month boy who was admitted to our hospital because of severe pneumonia and developed DRESS 3 weeks later. After the withdrawal of suspicious drug and administration of systemic corticosteroids, the patient's condition improved gradually. Nevertheless, hyperglycemia was detected 20 days after the initial onset of DRESS, and subsequent fulminant type 1 diabetes mellitus (F1DM) was diagnosed requiring continuous intravenous insulin infusion. After 13 months of follow-up, the blood glucose levels are now well-controlled. Literature research in PubMed for diabetes mellitus associated with DRESS showed 16 articles and 27 related case reports. Of 27 patients with DM related to DRESS, 11 were male, 16 were female. The mean age was 46 years. The duration from the onset of DRESS to the development of DM was 21 days on average. F1DM was diagnosed in 21 patients, T1DM was confirmed in 5 patients, and T2DM was only defined in 1 patient. Glutamic acid decarboxylase antibodies (GAD) were detected in 4 cases. Of 22 cases in which virus examination was carried out, evidence of virus reactivation was established in 16 cases (72.7%). Of patients with F1DM, 16 (88.9%) cases were evidenced by reactivation of herpes virus. A high frequency of HLA genotype and haplotype were found in 11 cases. DM was concomitant with acute pancreatitis in 3 patients and thyroiditis in 2 patients. No patients died from the disease. This work aims to raise awareness of long-term autoimmune sequelae in patients with DRESS.